New Testament Interpretation Through Rhetorical Criticism - Kennedy, George A. (George Alexander), 1928-2022 (Book collections on Project MUSE., 1984)
This book provides readers of the Bible with an important tool for understanding the Scriptures. Based on the theory and practice of Greek rhetoric in the New Testament, the book's approach acknowledges that New Testament writers wrote to persuade an audience of the truth of their messages. These writers employed rhetorical conventions that were widely known and imitated in the society of the times. Sometimes confirming but often challenging common interpretations of texts, this is a systematic study of the rhetorical composition of the New Testament.